ANALYSIS OF THE WELFARE OF TOBACCO FARMERS IN BANARAN VILLAGE, TEMBARAK DISTRICT, TEMANGGUNG REGENCY - Maman Faudzi; Khoirudin, Rifki; Afifah, Hasna Laili Nur; Abasimi, Ignatius (Jurnal Mebis, 2023)
Farmers' welfare plays an important role in increasing and maintaining agricultural production. Tobacco is one of the plants that has high value and is easy to grow in Indonesia and has an influence on society and economic development, especially agriculture. This study aims to determine whether income, land area, length of education, length of work, and household consumption affect the welfare of tobacco farmers in Banaran Village, Tembarak District, Temanggung Regency. The population in this study were the people of Banaran Village, Tembarak District, Temanggung Regency. The sample in this study used a purposive sampling method, namely 200 samples. This research uses descriptive analysis and multinomial logit test. The results of the research conducted showed that there were 2 variables that had a positive and significant influence, namely the variable land area of ​​0.034 and length of work variable of 0.048, while the variables that were not significant were income of 0.407, length of education of 0.209, and household consumption variable of 0.275. And for the simultaneous test all the independent variables used influence the welfare of tobacco farmers.